Kajian Hukum Terhadap Anak Yang Berhadapan Dengan Hukum Dalam Tindak Pidana Pencabulan - Sitohang, Edi Santro; Suhatrizal, Suhatrizal; Trisna, Wessy (Universitas Medan Area, 2021)
This type of research is normative research, namely research conducted with the aim of examining the application of statutory provisions in realizing justice. The descriptive nature of the analysis leads to normative law. The problems examined in this study are the legal protection of children who commit crimes of sexual abuse and consideration in deciding cases of child molestation which are analyzed from the legal protection of children. To discuss these problems, a library research was conducted and analyzed the decision case number 65 /pid-sus-anak/2015 /PN. Medan, at the Medan District Court. The results and discussion explain the legal protection of children who commit crimes of sexual immorality and the judge's considerations in deciding cases of child molestation, that the judge frees the defendant from all lawsuits from the crime of sexual abuse that the child has committed.